Gendered Perspectives on Fish Consumption: A Comparative Analysis of Women and Men in Kerala, India: Gender disparities in perception of fish consumers - Sajeev, M. V.; Joshy, C. G.; Gopal, Nikita (Fishery Technology, 2025)
The study conducted in Kerala, India aimed to assess consumption and perception differences among women and men fish consumers regarding health, safety, and quality issues. Using a purposive random sampling method, 263 women and 137 men fish consumers from coastal districts (Ernakulam and Kozhikode) and inland districts (Kottayam and Palakkad) of Kerala were surveyed. The sample represented a diverse range of socio-demographic characteristics, including gender, age, family size, education, occupation, and place of residence. Per capita fish consumption was estimated at 2.9kg/month with a household consumption of 11.6kg/month. Consumer perceptions reveal significant concerns about fish quality and safety and inefficiency of government mechanism in enforcement. The study found that women had a significantly higher perception than men regarding the nutrition and health benefits of fish, highlighting their efforts to meet the nutritional needs of their families. The findings suggest that while men may benefit from more customized information about the health advantages of fish, women may require tailored information on quality and safety risks associated with fish consumption. The study underscores the importance of customized scientific communication regarding the nutrition and health benefits of fish, specifically tailored for both genders.